How to Retain Quality under Expansion: Practices to Overcome Negative Consequences of Massification in Doctoral Education Original article - N G. Maloshonok; S. K. Bekova; S. V. Zhuchkova (Высшее образование в России)
As Russian and international experience shows, the massification of doctoral education is not only a driver of socio-economic development, but also a significant challenge for national policy in the field of higher education and research. The increase in demand for doctoral studies can lead to an enormous decrease in the quality of training unless particular measures for quality assurance and support are implemented. There are dozens of such practices worldwide. In this article, we consider three of them: 1) diversification of doctoral programs; 2) collaboration with industry and business; and 3) improving the quality of supervision. These practices have not yet been implemented in Russian doctoral programs on a systemic level. However, we believe that they are the most relevant and potentially useful for the Russian context, as they can improve the efficiency of doctoral training in terms of the number and quality of defenses, as well as increase the level of graduates’ preparation for the labor market.